El Mercantilismo. Teoría, política e historia - Rojas, Jorge (Economia, 2007)
Mercantilism was a very complex phenomenom and, as such, can be examined from different angles. To begin with, it is the first important chapter of the history of economic thought. Second, it can be studied —or criticized— by the theory of international trade, that usually opposes its own free trade philosophy to the mercantilist doctrines. And third, the mercantilist policies of the European powers —both colonial and noncolonial—, from the XVI to the XVIII century, constitute an important topic of the world economic history. Nevertheless, despite its complexity, mercantilist thought is usually presented in a very simple, almost naive, way: as a school that mistook precious metals for richness; that made the accumulation of those metals an end by itself, justifying with this purpose negative policies of protectionism and of intervention of the state in the economy. Here we will try to present mercantilism from its different angles, underlining its complexity, and emphasizing an aspect that it is not usually emphasized: the commercial colonial policies of the European powers from the XVI to the XVIII centuries. Finally, we make some questions on mercantilism, questions that we think have yet to be answered.